Product Market Competition and the Financing of New Ventures - de Bettignies, Jean-Etienne; Duchêne, Anne (Management Science, 2015)
This paper examines the interaction between venture risk, product market competition, and the entrepreneur’s choice between bank financing and venture capital (VC) financing. Under bank financing, a debt-type contract emerges as optimal, which allows the entrepreneur to retain full control of the venture and thus yields strong effort incentives, as long as the entrepreneur can service the debt repayment; however, this leads to liquidation in the case of default, making the venture’s success quite sensitive to exogenous, even temporary, shocks that may hinder debt repayment. Under VC financing, an equity-type contract emerges as optimal. Although it is not sensitive to exogenous shocks, this contract requires the entrepreneur to share a fraction of the rents with the financier, thus yielding lower effort incentives for the entrepreneur. There exists a threshold level of venture risk such that bank financing is optimal if and only if venture risk is below that threshold. Product market competition increases the value of stronger entrepreneurial incentives and thus increases the maximum level of risk the entrepreneur is willing to take before switching from bank financing to VC financing. This is a robust result that is shown to hold in various models of competition, including the Hotelling, Salop, Dixit–Stiglitz, and Cournot-to-Bertrand switch. This paper was accepted by Lee Fleming, entrepreneurship and innovation.